Hybrid Optimization‐Based Resource Allocation and Admission Control for QoS in 5G Network - Kumar, Kulbir; Noliya, Amandeep; Kumar, Dharmender; Mathur, Samiksha (International journal of communication systems, 2025)
ABSTRACT In the present world, network slicing is a viable approach to provide customized logical and digitalized applications in the fifth generation (5G). Furthermore, effective implementation of network slicing requires resource allocation (RA) and call admission control (CAC). As a result, this paper proposes the Al‐Biruni Remora Optimization Algorithm (BEROA)‐based RA and Deep Q Net (DQN)‐based CAC in a 5G network. The entire approach consists of 5G network simulation, optimal RA, and CAC. The 5G network simulation is the initial process, and the optimal RA is employed to allocate resources using the proposed BEROA. Furthermore, the DQN is utilized to perform the CAC using the user parameters like throughput, path loss, Reference Signal Received Power (RSRP), signal‐to‐interference‐plus‐noise ratio (SINR), and delay as well as the cell parameters like the count of users, cell throughput, cell power, and subcarrier power. After the admission of the new user in the cell, the count of active users in every cell is updated. Moreover, the BEROA + DQN‐based RA and CAC attain the finest throughput of 15.88 Mbps, delay of 0.232 s, number of user drops of 11.89, cell power of 0.264 dbm, call blocking probability of the new users of 9, 0.313, call blocking probability of the handoff users of 0.435, call dropping probability of the new users of 0.510, and call dropping probability of the handoff users of 0.474. This work proposes the effectual RA and CAC in the 5G networks. At first, a simulation of the 5G network is done. Following that, optimal RA is done by the proposed BEROA. Afterward, CAC is performed by the DQN with the user parameters like path loss of the user, RSRP, SINR, user throughput, and user delay, and the cell parameters like count of users, cell power, subcarrier power, and cell throughput. After admitting the new user, the counts of active users in the cells are upgraded.